MnTMPyP, a cell-permeant SOD mimetic, reduces oxidative stress and apoptosis following renal ischemia-reperfusion - Liang, Huan Ling (American Physiological Society, 2009)
Oxidative stress and apoptosis are important factors in the etiology of renal ischemia-reperfusion (I/R) injury. The present study tested the hypothesis that the cell-permeant SOD mimetic manganese(III) tetrakis(1-methyl-4-pyridyl)porphyrin (MnTMPyP) protects the kidney from I/R-mediated oxidative stress and apoptosis in vivo. Male Sprague-Dawley rats (175–220 g) underwent renal I/R by bilateral clamping of the renal arteries for 45 min followed by reperfusion for 24 h. To examine the role of reactive oxygen species (ROS) in renal I/R injury, a subset of animals were treated with either saline vehicle (I/R Veh) or MnTMPyP (I/R Mn) (5 mg/kg ip) 30 min before and 6 h after surgery. MnTMPyP significantly attenuated the I/R-mediated increase in serum creatinine levels and decreased tubular epithelial cell damage following I/R. MnTMPyP also decreased TNF-α levels, gp(91phox), and lipid peroxidation after I/R. Furthermore, MnTMPyP inhibited the I/R-mediated increase in apoptosis and caspase-3 activation. Interestingly, although MnTMPyP did not increase expression of the antiapoptotic protein Bcl-2, it decreased the expression of the proapoptotic genes Bax and FasL. These results suggest that MnTMPyP is effective in reducing apoptosis associated with renal I/R injury and that multiple signaling mechanisms are involved in ROS-mediated cell death following renal I/R injury.